Anticaries Potential of Temu Kunci-Serai Ethyl Acetate Extract Combination: In Vitro and Molecular Studies Approach - Priyadi, Muhammad; Saputra, Rizki Rachmad (Department of Chemistry, Faculty of Science and Technology Universitas Jambi, 2023)
Dental caries is one of the problems in dental disorders suffered by many people. There have been many ways of handling such as using temu kunci and lemongrass plants. This study aims to determine the antibacterial activity of caries in vitro and predict the mechanism of action of the bacteria that cause caries Streptococcus mutans. Temu kunci and lemongrass were extracted using ethyl acetate solvent. antibacterial tests against Streptococcus mutans were carried out using diffusion tests with a combination treatment of temu kunci: serai extracts 5% b/v: 5% b/v, 5% b/v: 10% b/v, and 10% b/v: 5% b/v. The positive control used amoxicillin and DMSO as a negative control. Potency as an anticaries drug of drived compound from Temu Kunci and Serai were evaluated by molecular docking using glucosyltransferase (3AIC). The results showed that the combination of temu kunci and serai with concentration 10% b/v: 5% b/v has potential as anticaries against Streptococcus mutans. Molecular studies depicted that Panduratin A, Isopanduratin, and 1,3-O-di-p-coumaroylglycerol have great activity toward 3AIC, respectively. Especially for Panduratin A and Isopanduratin, those compound depicted great and similar binding affinity (-8.4 kcal mol-1) that lower than Acarbose as native ligand (-8.3 kcal mol-1). Furthermore, those compound binding similarity ilustrated activity mechanism similarly with native ligand toward receptor. Additionally, the profiling drug-target interaction suggested Temu Kunci’s derived compounds have great potential as anticaries treatment.